Avaliação clínica e metabolômica da doença do enxerto contra o hospedeiro aguda em pacientes submetidos ao transplante de células tronco hematopoéticas - Ferreira, David Cavalcanti [UNIFESP] (2017)
Introduction: The main barrier to the success of hematopoietic stem cell transplantation (HSCT) is acute graft versus host disease (aGVHD). The risk factors for aGVHD are mainly clinical and can be improved if additional biological factors are incorporated, such as the metabolomic profile. Objective: To characterize the metabolic profile in serial form and the clinical evolution of patients submitted to HSCT. To assess whether metabolites identified in the plasma of patients prior to HSCT may reflect a risk factor in the development of GVHD. Method: Method: A prospective, randomized, observational study in which clinical evaluation and analysis of the plasma metabolomics of 26 patients (Group I) submitted to allogeneic HSCT at the Hospitals São Paulo and Santa Marcelina, with a 2-year follow-up after HSCT, were performed. The metabolomics study was carried out by Targeted Mass Spectrometry (uMol dosage of amino acids, biogenic amines, acetylcarnetines, phosphatidylcholines, sphingomyelins and hexoses) by Biocrates Life Science in Innsbruck - Austria. Samples from the 26 patients (Group I) collected before the conditioning regimen were called T1 and compared to the Group II (control) samples, consisting of a plasma biobank of 169 healthy individuals from the city of São Paulo. Group I was subdivided into subgroup IA: composed of 16 patients with aGVHD and subgroup IB: 10 patients without aGVHD. For both subgroups, serial samples were collected during transplantation, termed T1: before the conditioning regimen, T2: on the day of stem cell infusion, T3: at the moment of grafting, and the sample collected T4 was collected at the time of manifestation of aGVHD only for the subgroup IA only. Results: Most of the glycerophospholipids of the T1 samples were in reduced concentrations in the group of 26 onco-hematological patients submitted to transplantation when compared to the control group. When comparing the dosages of T1 samples of subgroup IA with those of subgroup IB, it was observed that the metabolites PCae40.1 and LysoPCaC18.2 had increased concentrations in the subgroup with aGVHD (IA), whereas the metabolites Nitrotirosina, PCae32 .1, PCa30.1 (p = 0.02), quinurenine, and the indole 2,3-dioxygenase enzyme were found to be decreased in T1-weighted samples in the subgroup with aGVHD (IA), these differences were statistically significant (p <0,05).Conclusion: Oncohaematological patients generally have glycerophospholipids in lower concentrations when compared to healthy subjects. This research identified that lower levels of quinurenine and the IDO enzyme in pretransplantion have been shown to be a risk factor for the development of aGVHD.